2017
DOI: 10.1016/j.bcp.2016.11.007
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro to in vivo extrapolation of the complex drug-drug interaction of bupropion and its metabolites with CYP2D6; simultaneous reversible inhibition and CYP2D6 downregulation

Abstract: Bupropion is a widely used antidepressant and smoking cessation aid and a strong inhibitor of CYP2D6 in vivo. Bupropion is administered as a racemic mixture of R- and S-bupropion and has stereoselective pharmacokinetics. Four primary metabolites of bupropion, threo- and erythrohydrobupropion and R,R- and S,S-OH-bupropion, circulate at higher concentrations than the parent drug and are believed to contribute to the efficacy and side effects of bupropion as well as to the CYP2D6 inhibition. However, bupropion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Recent studies have suggested that in vitro CYP downregulation by small molecules translates to clinical DDIs, 4,18,22 but the data on IVIVE of CYP downregulation are controversial. The data obtained here show that concurrent downregulation of CYP2D6 mRNA and induction of CYP3A4 in human hepatocytes in the absence of cytotoxicity does not unequivocally translate to in vivo DDIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that in vitro CYP downregulation by small molecules translates to clinical DDIs, 4,18,22 but the data on IVIVE of CYP downregulation are controversial. The data obtained here show that concurrent downregulation of CYP2D6 mRNA and induction of CYP3A4 in human hepatocytes in the absence of cytotoxicity does not unequivocally translate to in vivo DDIs.…”
Section: Discussionmentioning
confidence: 99%
“…The overall effect of the three compounds on CYP expression in vivo was predicted assuming that all three precipitants (13cisRA, atRA, and 4-oxo-13cisRA) bind to the same receptor to result in altered CYP expression via a competitive mechanism, as described previously. 18 The prediction for the change in exposure of the sensitive CYP2D6 probe substrate dextromethorphan following dosing of 13cisRA to steady state was performed as previously described 19 with an adaptation to account for the presence of m number of retinoids k each competing for binding to the receptor of interest:…”
Section: Prediction Of Ddismentioning
confidence: 99%
“…Investigators have reported downregulation of CYP450 gene expression, [29][30][31][32][33][34][35] some of which may be clinically relevant. For example, CYP2C9 downregulation has been observed in microarray analysis of human hepatocytes treated with A-792611 (10 µM, 48-hour treatments), a human immunodeficiency virus protease inhibitor and antagonist of the pregnane X receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional downregulation of P450s by chemicals was identified as an area requiring further exploration more than 10 years ago (Riddick et al, 2004). Despite this finding, published observations of druginduced downregulation by small molecules in vitro are scarce (Healan-Greenberg et al, 2008;Krausova et al, 2011;Yang et al, 2014;Zamek-Gliszczynski et al, 2014;Sager et al, 2017). Whereas potential mechanisms for downregulation have been identified (as detailed later herein), none has established a clinical effect for the major inducible enzymes (CYP1A2, CYP2B6, CYP2C, or CYP3A) from these in vitro observations.…”
Section: Discussionmentioning
confidence: 99%